D-Allulose (d-psicose) biotransformation from d-glucose, separation by simulated moving bed chromatography (SMBC) and purification by crystallization. (August 2022) - Wen, Xin; Ning, Yuhang; Lin, Huibin; Ren, Yilin; Li, Can; Liu, Yujie; Zhang, Chengjia; Lin, Jianqun; Lin, Jianqiang
Abstract: d -Allulose (or d -Psicose), a C-3 epimer of d -fructose, is a low-calorie rare sugar with excellent physiological functions. The recombinant Escherichia coli expressing d -allulose 3-epimerase for d -allulose conversion from d -fructose was constructed. Under the optimal conditions, 139.3 g/L d -allulose was produced from 500 g/L of d -fructose. In order to decrease the cost for mass production, one-pot reaction method by using immobilized glucose isomerase and recombinant E. coli expressing d -allulose 3-epimerase to produce d -allulose from d -glucose was developed. The immobilized glucose isomerase (200 g/L) and the recombinant E. coli cells (OD600 2) were mixed and used to transform d -glucose into d -allulose, and 228.5 g/L d -glucose, 216.3 g/L d -fructose and 90.7 g/L d -allulose were obtained from 550 g/L d -glucose after 3 h reaction. After that, d -allulose was separated from the reaction mixture by using simulated moving bed chromatography (SMBC) with the purity of 99.6%. Finally, crystallization was made to obtain the d -allulose crystals with 99.8% purity. The combination of enzyme and catalytic cells in biotransformation greatly expand the flexibility and capability of the catalytic reactions. This method developed in this study can be easily scaled up for mass production of highly purified d -allulose. Graphical Abstract: ga1 Highlights: Biotransformation of d -allulose from low cost d -glucose was realized. Separation of d -allulose were achieved by simulated moving bed chromatography. The practical process for mass production of d -allulose was established. Mixed biocatalysts increase the flexibility and capability of the catalyzation.